MACROZOOBENTHOS AND MICROZOOBENTHOS ABUNDANCE IN GROUND PEAT POND IN DIFFERENT BIOFERTILIZER - Harsadi, Asri; Hasibuan, Saberina; ', Syafriadiman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted from October to December 2016 in the Kualu Nenas village, Tambang Subdistrict, Kampar Regency, Riau Province. The aim of this research was to find out the influence of biofertilizer different to increasing the benthic abundance. The method this research is an experimental method using a Complete Random Design (CRD) with one factor, four treatments, and three replications. The treatment used were P0 (control / non biofertilizer) P1 (chicken fecal biofertilizer), (P2) cow fecal biofertilizer, and (P3) human fecal biofertilizer. Result of this research shown that the best of treatment was (P3) (human fecal biofertilizer) showed the 18.367 ind/m2 of macrozoobenthos abudance and the microzoobenthos abudance was the best on the P3 and P2 with is 32.653 ind/m2 respectively.Keywords : Biofertilizer, Macrozoobenthos, Microzoobenthos, Abundance ofMacrozoobenthos and abundance of Microzoobenthos